Présentation - Mattelart, Tristan (Questions de communication 45/2024: Journalisme culturel en mutation, 2024)
Présentation de l'article "Feeling and Playing the News: Conceptualizing Advances in Immersive and Gamified Journalism" par David O. Dowling